Cultural dilution in indirect Arabic translation of Indonesian popular literature: Laskar Pelangi to ‘Asākir Qaws Quzaḥ - Putri Nurmasyitah; Ridwan; Silmi Malina Binta; Ospan D. Kalmanbetuli (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Literary translation involves the transfer of linguistic meaning, as well as the cultural values and identities inherent in the source text. Translation difficulties increase in the realm of indirect translation, particularly when the target text is rendered through an intermediary language. This phenomenon is observed in the translation of Andrea Hirata's novel Laskar Pelangi into Arabic, ‘Asākir Qaws Quzaḥ, utilizing the English version, The Rainbow Troops. This translation process exemplifies multi-level translation, which may result in cultural dilution. This study aims to identify and analyse the manifestations of cultural dilution in indirect translation. This research employs a qualitative descriptive methodology within the framework of a descriptive translation study. The data sources comprise three parallel texts: Laskar Pelangi as the source text, The Rainbow Troops as the intermediary text, and ‘Asākir Qaws Quzaḥ as the target text. Data were gathered via document analysis by identifying cultural terms in the form of words, phrases, clauses, and sentences, and subsequently classified according to Newmark's cultural categories. The analysis was performed comparatively to identify changes in cultural significance. This study's results reveal that cultural dilution occurs in three primary forms: cultural deletion, cultural substitution, and cultural neutralization. The three forms illustrate the systematic and cumulative erosion of Indonesian cultural distinctiveness resulting from indirect translation. This research contributes to indirect translation studies by offering an analytical framework for cultural dilution and emphasising the significance of ideological awareness in cross-cultural literary translation practices.